Predictive Significance of the Monocyte-to-High-Density Lipoprotein Cholesterol Ratio in Post-Percutaneous Coronary Intervention Contrast-Induced Nephropathy Among Patients with Coronary Artery Disease - Lin A; Peng Y; Shao J; Chen L; Lin Y (Journal of Inflammation Research, 2025)
Aijie Lin,1,* Yanchun Peng,2,* Jiayi Shao,1 Liangwan Chen,3 Yanjuan Lin2,4 1School of Nursing, Fujian Medical University, Fuzhou, Fujian, People’s Republic of China; 2Department of Nursing, Fujian Medical University Union Hospital, Fuzhou, Fujian, People’s Republic of China; 3Department of Cardiac Surgery, Fujian Medical University Union Hospital, Fuzhou, Fujian, People’s Republic of China; 4Department of Cardiac Surgery Nursing, Fujian Medical University Union Hospital, Fuzhou, Fujian, People’s Republic of China*These authors contributed equally to this workCorrespondence: Liangwan Chen, Department of Cardiac Surgery, Fujian Medical University Union Hospital, No. 29 Xinquan Road, Fuzhou, Fujian, 350001, People’s Republic of China, Email fjxhlwc@163.com Yanjuan Lin, Department of Nursing, Fujian Medical University Union Hospital, No. 29 Xinquan Road, Fuzhou, Fujian, 350001, People’s Republic of China, Email fjxhyjl@163.comPurpose: This study aimed to examine the connection between monocyte-to-high-density lipoprotein cholesterol ratio (MHR) and contrast-induced nephropathy (CIN) and to introduce a novel perspective to early clinical diagnosis of CIN.Patients and Methods: This single-center bidirectional cohort study included 1771 patients with coronary artery disease (CAD) who underwent elective percutaneous coronary intervention (PCI) from January 2017 to July 2022 at the Fujian Medical University Union Hospital. The study collected data retrospectively through an electronic medical record system with postoperative follow-up. The primary endpoint was CIN, and secondary endpoints were mortality and readmission within two years after PCI, along with total days of hospitalization. Patients were divided into three groups based on preoperative MHR (Group 1: MHR < 0.42; Group 2: MHR ≥ 0.42 and < 0.64; Group 3: MHR ≥ 0.64). The study used regression analyses to investigate the relationship between MHR and CIN rate and postoperative mortality, and demonstrated the cumulative incidence of postoperative fatal events in the three groups of patients by Kaplan-Meier curves, and also analyzed the predictive value of MHR and other inflammatory indicators on the risk of CIN by using receiver operating characteristic (ROC) curves.Results: Compared to Group 1, Groups 2 and 3 had a higher incidence of CIN, higher mortality, and longer hospital stays (P < 0.001). Survival analysis showed significant differences in long-term mortality among the three groups (Log rank test, P = 0.032). Multivariate regression analysis showed that for every 1-unit increase in MHR, the risk of CIN increased 8.567-fold (95% CI: 4.291– 17.102, P < 0.001) and the risk of death increased 3.080-fold (95% CI: 1.423– 6.666, P = 0.004). ROC analysis showed that MHR had a good predictive ability for CIN (AUC: 0.713, 95% CI: 0.666– 0.759, P < 0.001).Conclusion: MHR is significantly linked to CIN and 2-year mortality following PCI in CAD patients, serving as a CIN risk assessment tool to assist clinics in early identification of high-risk patients and optimization of treatment strategies.Keywords: monocyte-to-high-density lipoprotein cholesterol ratio, inflammation, contrast-induced nephropathy, coronary artery disease, cardiovascular diseases, percutaneous coronary intervention